A case of oncocytic papillary cystadenocarcinoma of the parotid gland-Pathological and molecular features of a rare tumor - Shoko Kure, MD, PhD; Ryuichi Wada, MD, PhD; Wei-Xia Peng, MD, PhD; Hideaki Ishii, MD, PhD; Taeko Kitamura, MT; Takenori Fujii, MT; Shunta Inai, MD, PhD; Toshitaka Nagao, MD, PhD; Zenya Naito, MD, PhD (Elsevier, 2016)
We present histological, immunohistochemical and molecular features of oncocytic papillary cystadenocarcinoma, a rare neoplasm of the salivary and parotid glands, in an 82-year-old Japanese man. The resected tumor was solid nodular mass with fibrous capsule. The tumor was composed of papillary proliferation of tall columnar cells with thin vascular cores. The cytoplasm of the tumor cells was granular and eosinophilic. The tumor cells showed clear positive reaction for mitochondria and androgen receptor. GCDFP15 and HER2 were negative. Electron microscopy demonstrated numerous mitochondria in the cytoplasm of the tumor cells. Ki-67 index was 30%. Most of the tumor cells were positive for TP53, and single nucleotide polymorphism was found at codon 151. The invasion into the lymphatic spaces and capsule was noted. Although recurrence and metastasis were not noted at one and a half years after the resection, the patient needs to be followed up under careful observation.